2023
DOI: 10.1183/16000617.0173-2022
|View full text |Cite
|
Sign up to set email alerts
|

Endotyping COPD: hypoxia-inducible factor-2 as a molecular “switch” between the vascular and airway phenotypes?

Abstract: COPD is a heterogeneous disease with multiple clinical phenotypes. COPD endotypes can be determined by different expressions of hypoxia-inducible factors (HIFs), which, in combination with individual susceptibility and environmental factors, may cause predominant airway or vascular changes in the lung. The pulmonary vascular phenotype is relatively rare among COPD patients and characterised by out-of-proportion pulmonary hypertension (PH) and low diffusing capacity of the lung for carbon monoxide, but only mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 158 publications
(187 reference statements)
0
4
0
Order By: Relevance
“…This study also showed that HIF-2α overexpression was protective against the development of emphysema [48]. These observations lead to the hypothesis that HIF-2 transcription factors can control the genes that are involved in vascular remodeling and lung alveolar healing, which act as a molecular "switch", resulting in severe PH-COPD [13]. Further research is needed to define if HIF-2 augmentation or suppression can be used as therapeutic targets in severe COPD or pulmonary vascular phenotype, respectively.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This study also showed that HIF-2α overexpression was protective against the development of emphysema [48]. These observations lead to the hypothesis that HIF-2 transcription factors can control the genes that are involved in vascular remodeling and lung alveolar healing, which act as a molecular "switch", resulting in severe PH-COPD [13]. Further research is needed to define if HIF-2 augmentation or suppression can be used as therapeutic targets in severe COPD or pulmonary vascular phenotype, respectively.…”
Section: Discussionmentioning
confidence: 58%
“…Patients with severe PH-COPD may have predominantly circulatory limitations to their symptoms with signs of right ventricular failure and are phenotypically distinct from COPD without PH or mild PH. The hypoxia-inducible factor-2 is considered a possible molecular switch that may result in airway versus vascular remodeling [13].…”
Section: Introductionmentioning
confidence: 99%
“…Given their involvement in these crucial physiological processes, HIFs could potentially serve as biomarkers for certain lung conditions. However, further research would be required to confirm this hypothesis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The destruction of alveolar walls causes loss of elastic recoil, airway closure during exhalation, and air trapping in distal air spaces. Severe emphysema substantially affects patients' quality of life and is highly susceptible to a series of complications such as respiratory failure, which can be life-threatening (3). Most traditional interventions, such as oxygen inhalation combined with antispasmodic drugs and rehabilitation exercises, have minimal effects and fail to adequately control disease progression in patients with advanced emphysema (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%